The Influence of the School Literacy Movement on Students' Reading Interest - Juwita Ikhsanat Nirmala Zendrato; Novita Yanti; Yovita Florentina Telaumbanua; Fivin Aryanti Mendrofa; Agnes Renostini Harefa (Universitas Muhammadiyah Enrekang, 2024)
This study investigates the impact of the School Literacy Movement on students' reading interest in the educational context. Employing a quantitative approach with an associative method, the research aims to discern relationships between two or more variables, exploring roles, influences, and causative connections. The analysis employed in this research is the technique of simple linear regression, seeking to determine the influence of the school literacy movement on students' reading interest. The research findings indicate that the School Literacy Movement has a significant positive impact on students' reading interest. The strong correlation between participation in the school literacy movement and increased reading interest highlights the program's success in stimulating students' interest in literature. Consequently, the School Literacy Movement emerges as a crucial element in promoting students' reading interest, and these findings provide a foundation for the development of broader literacy strategies within the educational environment.